Laparoscopic sleeve gastrectomy modifies cholesterol synthesis but not cholesterol absorption. Issue 1 (January 2017) - De Vuono, S.; Ricci, M.A.; Siepi, D.; Boni, M.; Gentili, A.; Scavizzi, M.; Daviddi, G.; Labate, P.; Roscini, A.R.; Lupattelli, G.
Summary: Background and aims: Each bariatric surgery procedure impacts differently on cholesterol synthesis and absorption. Although a restrictive procedure, sleeve gastrectomy resolves diabetes mellitus and, like mixed-type procedures, induces early changes in gastrointestinal hormones. To our knowledge the present study is the first to assess the effects of sleeve gastrectomy on cholesterol synthesis and absorption. Methods and results: 42 consecutive subjects with obesity and sleeve gastrectomy candidates were included in the study together with a control group of 20 subjects without obesity. Before sleeve gastrectomy and 10 months afterwards, all subjects underwent a clinical examination, blood tests, ultrasound visceral fat area estimation and determination of plasma lathosterol, campesterol and sitosterol concentrations. After sleeve gastrectomy, significant decreases were observed in BMI, waist circumference, visceral and subcutaneous fat, blood pressure, triglycerides, insulin and glucose levels, lathosterol and HOMA-IR. HDL-C and apolipoprotein AI levels increased significantly. No significant differences emerged in LDL-C, apolipoprotein B levels or cholesterol absorption markers. Lathosterol levels correlated significantly with BMI, visceral fat area and HOMA-IR. Differences in cholesterol intake after surgery were not significantly associated with differences in lathosterol, campesterol and sitosterol concentrations. Conclusions: Sleeve gastrectomy reduced the markers of cholesterol synthesis but did not modify cholesterol absorption. Changes in cholesterol synthesis and absorption were independent of variations in cholesterol intake, suggesting a specific sleeve gastrectomy-related effect.